CONSUMER PSYCHOLOGY – SCIENCE AND PRACTICE THE INFLUENCE OF PSYCHOLOGY AND NEUROMARKETING ON CONSUMER BEHAVIOR - Stanišić, Snježana (ACADEMIC REVIEW, 2025)
Behavioral economics deals with the relationship between emotions and mental frameworks that influence consumer decision-making. The essence of this discipline lies in the ability to assess the value of a particular event and to choose between different options. Research conducted in this and related areas deepens the understanding of consumer psychology, providing practical insights for marketers and sellers who aim to adapt their products and marketing activities to the psychological states of consumers. Based on the findings of how consumers make decisions on a subconscious level – regarding what to buy, where to buy, and when to buy – a new scientific discipline has emerged in marketing: neuromarketing. The main task of neuromarketing is to determine the factors that influence a consumer’s decision to purchase a specific product or service. This paper focuses on the consumer, their reactions, relationships, and emotions in various situations to which they are frequently exposed. To support this, a survey was conducted among a number of consumers, who responded to questions that were predominantly psychological in nature. Key words: Consumer psychology, neuromarketing, emotions, behavioral economics